2020
DOI: 10.3390/pharmaceutics13010043
|View full text |Cite|
|
Sign up to set email alerts
|

Multifaceted Factors Causing Conflicting Outcomes in Herb-Drug Interactions

Abstract: Metabolic enzyme and/or transporter-mediated pharmacokinetic (PK) changes in a drug caused by concomitant herbal products have been a primary issue of herb and drug interactions (HDIs), because PK changes of a drug may result in the alternation of efficacy and toxicity. Studies on HDIs have been carried out by predictive in vitro and in vivo preclinical studies, and clinical trials. Nevertheless, the discrepancies between predictive data and the clinical significance on HDIs still exist, and different reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Considering that numerous reports the inhibitory effects of mangosteen pericarp extract and xanthones as main components of mangosteen pericarp extract against P-gp [61,62], the increased donepezil concentration in the brain may be due to the inhibition of P-gp-mediated donepezil efflux through BBB by WMP. Although P-gp is expressed in many other organs, the degree of P-gp inhibition by P-gp inhibitors are different because the concentrations of P-gp inhibitor in the specific tissue are various, with different inhibiting P-gp activities [61,63,64]. In this view, WMP might significantly inhibit only P-gp mediated donepezil efflux through BBB, not in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that numerous reports the inhibitory effects of mangosteen pericarp extract and xanthones as main components of mangosteen pericarp extract against P-gp [61,62], the increased donepezil concentration in the brain may be due to the inhibition of P-gp-mediated donepezil efflux through BBB by WMP. Although P-gp is expressed in many other organs, the degree of P-gp inhibition by P-gp inhibitors are different because the concentrations of P-gp inhibitor in the specific tissue are various, with different inhibiting P-gp activities [61,63,64]. In this view, WMP might significantly inhibit only P-gp mediated donepezil efflux through BBB, not in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not strong scientific evidence that supports any claim of efficacy of herbal supplements in the management of viral infections such as COVID-19, their use is prevalent in many countries, especially in the Far East [ 10 , 11 , 12 , 13 , 14 ]. These practices continue despite the fact that the use of herbs and bioactives has the potential to lead to pharmacokinetic or pharmacodynamic changes in many commonly used medications, particularly in the elderly [ 15 ]. Moreover, the WHO reported that the use of traditional and complementary medicine varies widely throughout the world and ranges from 1% to 99% of the population depending upon the country and local customs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human medical metabolism studies of natural products are usually limited to the secondary metabolites, which are used as single-substance drugs, e.g., in cancer therapy, as anti-infectives or as immunosuppressants [ 8 ]. The metabolic fate of compounds from herbal medicines (“botanicals”) is not well covered by research [ 9 , 10 ], although its importance is understood [ 11 , 12 , 13 , 14 ]. The lack of data on, and lack of understanding of, the pharmacokinetic interaction of herbal drug constituents with the drugged organism is known as one of the major hurdles in the development of herbal medicines as fully accepted mainstream drugs/therapeutics.…”
Section: Introductionmentioning
confidence: 99%